2015
DOI: 10.1515/pjvs-2015-0096
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary supplementation with sage (Salvia officinalis L.) essential oil on antioxidant status and duodenal wall integrity of laying strain growers

Abstract: The objective of this study was to compare the influence of four different concentrations of Salvia officinalis essential oil (EO) on animal health. A total of 50 laying strain chicks were randomly divided at the day of hatching into five dietary-treatment groups. Control group was given the basal diet (BD), the other four experimental groups contained BD supplemented with 0.1, 0.25, 0.5, 1.0 g S. officinalis EO/kg diet, respectively. 0.1 g/kg EO increased glutathion peroxidase activity (GPx) in duodenal mucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…These results are in accordance with previous studies [59][60][61], where essential oils increased the antioxidant effects in in vitro and in vivo systems (HepG2, IEC-6, hepatocytes of rat and mice). The results of Placha et al [62] demonstrated that lower concentrations of EOs improve the health status of animals. Total antioxidant status in plasma significantly increased in a group of birds with their diet supplemented with an EO (sage oil).…”
Section: Discussionmentioning
confidence: 99%
“…These results are in accordance with previous studies [59][60][61], where essential oils increased the antioxidant effects in in vitro and in vivo systems (HepG2, IEC-6, hepatocytes of rat and mice). The results of Placha et al [62] demonstrated that lower concentrations of EOs improve the health status of animals. Total antioxidant status in plasma significantly increased in a group of birds with their diet supplemented with an EO (sage oil).…”
Section: Discussionmentioning
confidence: 99%
“…Plant-derived essential oils and lipid-soluble bioactive compounds have gained attention for biological roles due to their higher bioavailability compared to water-soluble bioactive compounds. Recently, some essential oils extracted from plants have been reported to have antioxidant effects through scavenging radicals and inducing antioxidant enzymes [17][18][19]. Lavandula angustifolia (true lavender or English lavender) is a well-known aromatic plant rich in volatile oil which is frequently reported to contain linalool (20-50% of the fraction) and linalyl acetate (25-46% of the fraction) as the major oil constituents [20].…”
mentioning
confidence: 99%
“…Moreover, 0.25 g/kg EO increased GPx in the liver, total antioxidant status (TAS) in plasma, PA in blood, and TEER in duodenal tissue. As a conclusion, lower concentrations of EO were found to improve the animalsʼ health status [79].…”
Section: Antioxidant Activity Of Sage: In Vivo Animal Studiesmentioning
confidence: 80%